International Terrorism, Domestic Political Instability, and the Escalation Effect. (6th February 2013) - Campos, Nauro F.; Gassebner, Martin
<x xml:space="preserve">Abstract</x> What are the main causes of international terrorism? Despite the meticulous examination of various candidate explanations, existing estimates still diverge in sign, size, and significance. This article puts forward a novel explanation and supporting evidence. We argue that domestic political instability provides the learning environment needed to successfully execute international terror attacks. Using a yearly panel of 123 countries over 1973–2003, we find that the occurrence of civil wars increases fatalities and the number of international terrorist acts by 45%. These results hold for alternative indicators of political instability, estimators, subsamples, subperiods, and accounting for competing explanations.